2021
DOI: 10.1186/s12877-021-02105-0
|View full text |Cite
|
Sign up to set email alerts
|

Technology-driven solutions to prompt conversation, aid communication and support interaction for people with dementia and their caregivers: a systematic literature review

Abstract: Background The impact of dementia for communication skills can result in difficulties in social interactions between people with dementia and their conversation partner, as initiating and maintaining conversations becomes increasingly challenging. The role of technology in enhancing social health and participation for people with dementia is increasing, but the use of technological devices to support social interactions and aid communication quality is still in its infancy. The objective of thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
1
27
0
2
Order By: Relevance
“…help PLWD socialize with family and friends, thereby imparting positive emotions and reducing anxiety and agitations [ 72 , 73 ]. Furthermore, one of the recent review works has presented the existing technical solutions to aid communication skills for the people with dementia [ 100 ]. The review work pointed out that the PLWD lack communication skills, which hinder their social interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…help PLWD socialize with family and friends, thereby imparting positive emotions and reducing anxiety and agitations [ 72 , 73 ]. Furthermore, one of the recent review works has presented the existing technical solutions to aid communication skills for the people with dementia [ 100 ]. The review work pointed out that the PLWD lack communication skills, which hinder their social interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, more research is required in this area. There are certain devices that can aid the PLWD having language impairment, through social interactions and human computer interactions [ 100 , 103 ]; however, such devices need more systematic trials and user testing at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…An app may also have the potential for further customization of the intervention, thus making it more person-centered. This study also has the potential to address the gap identified by Hoel et al [ 42 ] in a systematic literature review that found a lack of good quality research in the use of technological devices to support communication and meaningful social interactions between PWD and their (in)formal carers. According to the review, tablet computers that ran apps designed for reminiscence activities for PWD were the most common device used to facilitate communication between PWD and their (in)formal carer.…”
Section: Introductionmentioning
confidence: 99%
“…According to the review, tablet computers that ran apps designed for reminiscence activities for PWD were the most common device used to facilitate communication between PWD and their (in)formal carer. Hoel et al noted that most of the studies that were included in the review did not mention frequencies and duration of the interventions, and only two out of the seven studies that used a tablet computer included a control condition [ 42 44 ]. In addition, among studies in the review that used tablet computers in a nursing home [ 45 – 47 ], most of it involved a small number of residents with dementia [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation